Intestinal obstruction in pregnancy: three case reports - Maheswari S, Latha; Abraham, Reena; Chitra, T. V. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
The occurrence of intestinal obstruction is uncommon in pregnancy and so it is rarely considered as a cause for acute abdominal pain. It is also a life threatening condition to the mother if proper medical intervention is delayed. In this review we present three cases of intestinal obstruction during pregnancy and puerperium. The incidence in our tertiary care center over a period of last 5 years is 1 in 3196 deliveries. These cases were diagnosed preoperatively with x-ray and sonogram. Laparotomy with definitive surgical treatment was performed. The first patient had large bowel obstruction due to sigmoid volvulus, the second patient had a stricture in ileum leading to small bowel obstruction, and the third patient had ileocecal intussusception. There were no maternal deaths but one patient had fetal loss.